Comparative of Student Learning Outcomes: Practice Rehearsal Pairs Learning Strategy with Index Card Match - Syamsiah Syamsiah (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: This study aims to compare the student learning outcomes between two different learning strategies: Practice Rehearsal Pairs (PRP) with Index Card Match (ICM) in the context of Digestive System material. Methodology: This study uses a quasi-experimental approach with a Nonequivalent Control Group design. The population in this study were all students of grade XI of Public High School 1 Muara Enim totaling 5 classes. Sampling was done using simple random sampling technique in two experimental classes. Data collection was done using multiple-choice tests and analyzed using descriptive and inferential statistical techniques. Main Findings: The results of the study obtained for both groups through descriptive statistical analysis are that the average biology learning outcomes using the Practice Rehearsal Pairs learning strategy are better than using the Index Card Match learning strategy. The results of the inferential data analysis show that there is a significant difference between the use of the Practice Rehearsal Pairs learning strategy and the Index Card Match learning strategy on the biology learning outcomes of class XI students. Novelty/Originality of this study: This type of research has the potential to provide insight into the relative effectiveness of two different learning approaches in facilitating student understanding and learning outcomes on a particular topic. with the Practice Rehearsal Pairs and Index Card Match approaches likely focusing on learning methods in which students pair up to practice and repeat material together.